2021
DOI: 10.1111/tmi.13551
|View full text |Cite
|
Sign up to set email alerts
|

Spatial pattern and determinants of HIV infection among adults aged 15 to 54 years in India – Evidence from National Family Health Survey‐4 (2015‐16)

Abstract: objective To assess the spatial pattern and determinants of HIV infection in India. methods We conducted a secondary data analysis using the National Family Health Survey-4 data obtained from the Demographic Health Survey programme. We accounted for clustering and stratification in the sampling design using the svyset command. Spatial analysis was performed by generating the Moran's I statistic and local indicators for spatial association (LISA) maps. Logistic regression was performed to identify the determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A study in Rio de Janeiro highlighted the association between urbanization and a high HIV incidence rate 33 . Geographical clustering is a common phenomenon in urban areas and has also been identified in other countries such as India and Ethiopia 34,35 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A study in Rio de Janeiro highlighted the association between urbanization and a high HIV incidence rate 33 . Geographical clustering is a common phenomenon in urban areas and has also been identified in other countries such as India and Ethiopia 34,35 .…”
Section: Discussionmentioning
confidence: 85%
“…The economic, demographic, and social dynamics of the coastal region are influenced by the dynamism of the Port of Paranaguá, and other factors such as the location of the state's major roadways, high fluctuating population density, mobility, seasonal labor migration, and tourism are elements that can contribute to the propagation and maintenance of HIV 34,37 . These characteristics, also recognized in border regions, represent critical points facilitating multiple casual partners, unprotected sexual relations, drug concentration, and sexual exploitation 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of STI/RTI ranged from 11–17% in Andhra Pradesh, Maharashtra, Rajasthan and Jharkhand to 21–22% in Bihar and Tamil Nadu among the study participants [ 60 ]. The overall prevalence of HIV infection among the general population in India was reportedly 0.24% (95% CI: 0.21%–0.28%) [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Key determinants influencing sexual risk behaviours and the vulnerability of AGYW to STIs and HIV are primarily rooted in socioeconomic contexts, relationship dynamics, proximal factors, substance use, and awareness levels about STIs/HIV [30, 39,44,56,[73][74][75][76][77][78][79]. Socioeconomic factors such as age, educational attainment, marital status, economic status, and PLOS ONE overall living conditions significantly dictate the vulnerability of AGYW to these health risks [4,10].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also concluded that TB is strongly associated with poverty and poor living conditions. [38][39][40] In South Korea and Northeast Brazil, demographic and socioeconomic conditions had strong explanatory power in making spatial differences in TB incidence. TB was more prevalent in areas with poor socioeconomic levels and high population density.…”
mentioning
confidence: 99%